Transparency-based protocol for decision-making regarding seismic rehabilitation projects of public buildings - Santa-Cruz S. (2021)
Motivation and problem definition: A large number of public buildings designed with obsolete criteria are at high seismic risk and in need of structural rehabilitation. The task of selecting the optimal strategy poses important challenges for decision-makers due to the variety of intervention options and the fact that the construction sector is perceived to be one of the most corrupt in the economy. Objective: Given that transparency is an efficient anti-corruption strategy, a protocol is proposed for decision-making in seismic rehabilitation projects of public infrastructure that incorporates criteria which serve to increase transparency in the project development. Methods: Firstly, the literature was reviewed to describe current practices and regulations linked to decision-making in seismic rehabilitation/retrofitting of buildings. Secondly, relevant criteria that should be taken into account to favor transparency in decision-making were proposed. Thirdly, these criteria were integrated into a protocol that uses information and communication technologies (ICTs), Building Information Modeling (BIM), and collaborative methodologies that involve all stakeholders that will participate in the decision-making process. Finally, the protocol was applied to a real decision-making case study for the selection of alternatives for large-scale reinforcement of state schools in the city of Lima. Results: The criteria of auditability or ease of control of the construction process is well regarded by stakeholders as a mechanism to increase transparency. Including these transparency criteria could influence the selection of reinforcement alternatives, especially if the profile of stakeholders is environmentally-oriented. The sensitivity analysis confirmed the dependency of the selection on the decision-maker profile. © 2021 Elsevier Ltd